2020
DOI: 10.21203/rs.3.rs-26172/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between the non-HDLc-to-HDLc ratio and carotid plaques in a high stroke risk population: a cross-sectional study in China

Abstract: Background Evidence on the association between the non-high-density lipoprotein cholesterol (non-HDLc)-to-high-density lipoprotein cholesterol (HDLc) ratio (non-HDLc/HDLc) and carotid plaques is still limited. We aimed to assess the relationship between the non-HDLc/HDLc and carotid plaques in a population with a high risk of stroke. Methods A cross-sectional study based on the community was conducted in Yangzhou, China. Residents (no younger than 40 years old) underwent questionnaire interviews, physical ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recent evidence also suggests that the non‐HDL‐C‐to‐HDL‐C ratio indicates combined lipid problems and has been shown to be a better predictor of multiple dyslipidaemia‐related diseases 15 . There have been studies reporting that non‐HDL‐C‐to‐HDL‐C ratio is a useful predictor for coronary heart disease, metabolic syndrome and insulin resistance 16‐18 . Moreover, a retrospective cohort study found that subjects with higher non‐HDL‐c/HDL‐c ratio had a higher risk of NASH 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence also suggests that the non‐HDL‐C‐to‐HDL‐C ratio indicates combined lipid problems and has been shown to be a better predictor of multiple dyslipidaemia‐related diseases 15 . There have been studies reporting that non‐HDL‐C‐to‐HDL‐C ratio is a useful predictor for coronary heart disease, metabolic syndrome and insulin resistance 16‐18 . Moreover, a retrospective cohort study found that subjects with higher non‐HDL‐c/HDL‐c ratio had a higher risk of NASH 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, sd-LDL-cholesterol is a more sensitive biomarker for the prediction of atherosclerotic CVDs in T2DM than LDL-c [42]. Yan Liu et al found a positive relationship between the non-HDL-c/HDL-c ratio and carotid plaques among Chinese [43]. In a study conducted by Zhao et al, non-HDL-c/HDL-c was found to be superior to the traditional lipids for evaluating the degree of atherosclerosis among middle-aged and elderly patients in China [36].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the ratio of non-highdensity lipoprotein cholesterol to high-density lipoprotein cholesterol (NHHR) has attracted increasing attention, and many studies have proposed that it can reflect the relationship between mixed blood lipids, better reflect the balance between atherosclerosis and anti-atherosclerosis, and better reflect dyslipidemia than the traditional blood lipid spectrum. NHHR has been found to be significantly associated with a variety of lipid abnormality-related diseases such as atherosclerotic plaques [5], metabolic syndrome, insulin resistance [6,7], nonalcoholic fatty liver [8], and chronic kidney disease [9]. Numerous studies have shown that NHHR can better assess the severity of coronary artery disease and cardiovascular adverse events than LDL-C, HDL-C, non-HDL-C, LDL-C/HDL-C, and other single indica- tors [10,11].…”
Section: Introductionmentioning
confidence: 99%